The effect of self-education on teachers’ competitiveness - Larysa Gorodnycha; Svitlana Gergul; Maryna Olkhovyk; Valentyn Panchenko; Iryna Turchyna (Intelektual Pustaka Media Utama, 2023)
Lifelong learning skills and building competencies necessary for teachers’ competitiveness are urgent issues. This work aimed to study the relationship between teachers’ self-education and competitiveness. The research method used a questionnaire survey of teachers and principals of general secondary education institutions, as well as the method of comparison and mathematical methods. The results showed that there was a relationship between teachers’ motivation factors for independent lifelong learning, directions and sources with the achieved results of self-education was established. According to the framework of competitive competencies, the teacher’s qualities’ dependence on motivation, directions, sources and results of self-education was also revealed. The results of this study can be helpful as they arrange knowledge and research methods of the self-education process, taking into account motivation, directions, sources, and outcomes. Therefore, teachers should engage in self-education throughout their professional life to improve their competitiveness. They should also constantly update their knowledge of the fields related to teaching. They must develop synchronously with the evolution of science and technology and have a creative approach to learning. Teachers should supplement their knowledge of subject teaching methods, psychology, and health care. Further research should focus on other factors influencing improving teachers’ competitiveness.